HUBUNGAN KUALITAS TIDUR TERHADAP KECEMASAN PADA LANSIA DI POLI GERIATRIK RSUD INDRASARI RENGAT - Rahmaniza, Rahmaniza; Fadhli, Rohmi; Nazarudin, Etin; Harlia Putri, Triyana (Jurnal Ilmu Keperawatan, 2023)
The development of individuals ends with last step of being elderly. Along with increasing age, a decrease in body function in the elderly, both physically, physiologically and psychologically. The psychological problem that often occurs in the elderly is anxiety. Unresolved anxiety experienced by the elderly will disrupt the quality of sleep for the elderly. The purpose of this study was to determine the relationship between sleep quality and anxiety in the elderly at the Geriatric’s Poli. This study used a descriptive correlational method, with a cross sectional survey desingn, with a total sampling technique. The Samples in this study were all elderly who went to the Geriatric Clinic, with a total sample of 106. The data analysis used chi-square test. The results showed that the average elderly experienced poor sleep quality, namely84 people (79,2%), while 56 people ( 52,8%) experienced moderate anxiety. There is a relationship between sleep quality and anxiaety in the elderly at the Geriatric Clicic of Indrasari Rengat Hospital, with a correlation value of p value (0,010). Recommended to the elderly will remain active in carrying out their activities and maintain their health, and reduce stress in the elderly.